CHILDREN'S POSITIVE SCHOOL BEHAVIORS AND SOCIAL PREFERENCE IN URBAN ELEMENTARY CLASSROOMS. Issue 2 (March 2014) - Torrente, Catalina E.; Cappella, Elise; Watling Neal, Jennifer
<x xml:space="preserve">Abstract</x> This study examined the associations between prosocial and academically oriented behaviors and social preference as a function of individual (i.e., gender), developmental (i.e., grade) and contextual factors (i.e., group descriptive norms). Data were gathered from a sample of 2nd, 3rd and 4th grade children (51% male, 97.5% African American) in 34 classrooms from high‐poverty inner‐city neighborhoods. Multilevel analyses indicated that individual, developmental, and contextual factors moderated the association between children's prosocial and academically oriented behaviors and social preference. Taken together, results from this study support theoretical models emphasizing the relational and contextual nature of children's social preference in the peer group.